Analisis Kesalahan Siswa Kelas VIII pada Bangun Ruang Berdasarkan Teori Nolting dan Scaffolding - Anggita Oktaviana Putri; Ayu Imtyas Zahrotut Thoyiba (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2026)
Student error analysis is an activity to investigate errors or deviations made by students in solving problems, both systematically and consistently. The purpose of this error analysis is to help teachers identify the extent of students' abilities in solving a problem. This study aims to describe the errors made by students and efforts to provide scaffolding or assistance. This study was conducted at SMP Bhakti Turen, with 25 eighth-grade students. The method used was qualitative research with a descriptive approach. In this study, three subjects were taken, representing the high, medium, and low levels of error categories. The data collection techniques used were tests and interviews. The data analysis techniques used were analysis of test scores and interviews. The data validity technique used was a credibility test. The results showed that subjects in the high error rate category made several errors, namely carelessness, conceptual errors, and conceptual application errors. Subjects in the moderate error rate category made two errors, namely carelessness and conceptual application errors. Subjects in the low error rate category made one error, namely carelessness. Based on the results of this research, teachers can provide scaffolding or assistance so that students can correct the mistakes they make.